Photoinactivation of Candida albicans using methylene blue as photosensitizer - SOUSA,João Nilton Lopes de (2015)
Objective: To evaluate the effect of photodynamic therapy in the inactivation of Candida albicans planktonic cells, using methylene blue, 150 mg/mL, as a photosensitizer. Methods: Aliquots of 100 (μg/mL of the fungal suspension in a 106 cells/mL concentration were seeded in microtiter plates with 96 wells, where the same volume of methylene blue was deposited, remaining for 5 min pre-irradiation. Then, the low power laser light was applied (wavelength: 660 nm, power: 100 mW and dose: 426 J/cm2) for 128s using a portable semiconductor laser. Control experiments were performed without illumination and in the absence of methylene blue, and another in the presence of methylene blue without illumination and with illumination, replacing the photosensitizer by saline. In each experimental condition, serial dilutions (10-1 to 10-3) were obtained and 25 μL aliquots were seeded in Sabouraud Dextrose Agar duplicate. After this period, the number of colony forming units per milliliter (CFU/mL) was determined and the data were submitted to variance analysis and Kruskal Wallis test (p <0.05). Results: At the concentration of 150 μg/mL, and time of 5 min incubation, the reduction was significant (p˂0.05). In the absence of irradiation, methylene blue produced no reduction in CFU/mL. Conclusion: Photodynamic Therapy presented antifungal effect against Candida albicans and can be used as an adjunct to conventional treatment.